Successful Treatment of Paraneoplastic Dermatomyositis using a Novel IVIg Preparation - A Case Report - Kälber, Katharina A; Enk, Alexander H; Winkler, Julia K (Archives of Clinical and Medical Case Reports, 2025)
Dermatomyositis belongs to the group of idiopathic inflammatory myopathies (IIMs). The annual prevalence in adults is 6-7 per 100.000 population. Clinical manifestations include characteristic skin lesions and a progressive muscle weakness. Rapid and sufficient immunosuppressive treatment is demanded. Most patients receive a first-line therapy with oral glucocorticoids. Because of the systemic side effects, steroid-sparing therapy is added. Especially for severe or refractory disease high-dose intravenous immunoglobulins (IVIgs) at a dose of 2 g per kg bodyweight distributed over 2 to 5 days every 4 weeks are a promising and welltolerated treatment option. We report the case of a 75-year-old female patient suffering from severe paraneoplastic dermatomyositis. She achieved significant improvement of skin and muscle symptoms during therapy with a new IVIg preparation, which was very tolerated. Unfortunately, she died four months later since therapy of her lung tumor was refused.